1980
DOI: 10.1177/028418518002100608
|View full text |Cite
|
Sign up to set email alerts
|

Angiography of the Ovarian Artery in Adnexal Lesions

Abstract: Selective catheterization of the ovarian artery was performed in 39 women with pelvic tumor. Previously the combination of ultrasound and bilateral selective internal iliac angiography was proven to be valuable in the evaluation of gynecologic lesions. The present series demonstrates that selective ovarian angiography still enhances the possibilities for a correct preoperative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…On the other hand, our study could just as well have shown that the 3D power Doppler method was too crude to detect the differences. Earlier studies found a wide heterogeneity of vessel distribution in different parts of tumors38, 39 and in different types of tumor37, 40, 41. Such heterogeneity may explain some of the false‐positive and false‐negative diagnoses using our technique.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, our study could just as well have shown that the 3D power Doppler method was too crude to detect the differences. Earlier studies found a wide heterogeneity of vessel distribution in different parts of tumors38, 39 and in different types of tumor37, 40, 41. Such heterogeneity may explain some of the false‐positive and false‐negative diagnoses using our technique.…”
Section: Discussionmentioning
confidence: 65%
“…A vessel size equal to or larger than the 4-F catheter used (diameter, 1.3 mm) served as the threshold, since in the absence of ovarian or uterine disease the ovarian artery seldom exceeds 1 mm in diameter (22).…”
Section: Discussionmentioning
confidence: 99%
“…UOA usually exists anatomically, but the frequency of visualizing UOA by arteriography is low [10]. It is hypertrophied in the presence of uterine or ovarian lesions [9,10]. In previous studies, UOAs were.…”
Section: Discussionmentioning
confidence: 97%
“…UOA is considered a cause of technical and ovarian failure after UAE [6]. Previous studies have shown that UOA detected by uterine angiography or aortography is associated with repeated UAE and ovarian dysfunction [1,[7][8][9]. UOA usually exists anatomically, but the frequency of visualizing UOA by arteriography is low [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation